2009
DOI: 10.1080/01902140802712738
|View full text |Cite
|
Sign up to set email alerts
|

Common Pathways for Activation of Proinflammatory Gene Expression by G Protein–coupled Receptors in Primary Lung Epithelial and Endothelial Cells

Abstract: Acute lung injury is associated with an inflammatory response resulting from the action of multiple mediators. Many proinflammatory mediators released during lung injury exert effects by binding to G protein-coupled receptors (GPCRs). Our earlier studies showed that substance P (SP), a ligand for the tachykinin 1 receptor, induced NF-κB activation and IL-8 upregulation through a Gq-dependent pathway. Here we extend these findings by examining effects of multiple ligands for Gq-coupled GPCRs in primary human sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…To examine this, we screened several ligands that are coupled to the generation of IP 3 in NHBE cells. Although several receptors coupled to PLC-IP 3 signaling are thought to be expressed in AECs (30), this screen revealed that only a subset of ligands, including agonists for PAR2 and purinergic P2Y receptors (and to a smaller extent, thrombin and bradykinin) evoked Ca 2+ signals consistent with store-operated Ca 2+ entry (Table I). PAR2 receptors are important for the ability of AECs to sense allergens and endogenous proteases and for mediating the subsequent inflammatory responses in the lung (31).…”
Section: Resultsmentioning
confidence: 99%
“…To examine this, we screened several ligands that are coupled to the generation of IP 3 in NHBE cells. Although several receptors coupled to PLC-IP 3 signaling are thought to be expressed in AECs (30), this screen revealed that only a subset of ligands, including agonists for PAR2 and purinergic P2Y receptors (and to a smaller extent, thrombin and bradykinin) evoked Ca 2+ signals consistent with store-operated Ca 2+ entry (Table I). PAR2 receptors are important for the ability of AECs to sense allergens and endogenous proteases and for mediating the subsequent inflammatory responses in the lung (31).…”
Section: Resultsmentioning
confidence: 99%
“…Without causing toxicity, the secretion of GM-CSF and TNF-␣ were almost completely abolished, suggesting the importance of PKC in PAR2-mediated GM-CSF and TNF-␣ secretion. Recent studies have also shown the important involvement of PKC in PAR2-induced inflammation (2,10).…”
Section: Discussionmentioning
confidence: 97%
“…Physiological and pathological effects of PAF are mediated by its specific G protein coupled receptor reported to be G q (30,31). We have shown in previous reports that PAF induces expression of its own receptors in vivo and in vitro suggesting that PAF activates intracellular molecules that regulate gene expression and cell growth (9,23).…”
Section: Discussionmentioning
confidence: 99%